Dawson's Creek : The Complete Second Season Disc 2 - Whitmore, James; Holmes, Katie (USA Sony Pictures, 1998)
Set in a small coastal, Massachusetts town named Capeside, Dawson's Creek tells the story of four teenagers as they struggle through adolescence. This is particularly true for 15-year-olds Dawson Leery (James Van Der Beek), an introspective dreamer and Joey Potter (Katie Holmes), a precocious tomboy unaware of her beauty. Best friends since childhood, they are about to enter that confusing time in life where nothing is the way it was and nothing is as it seems.
Languages: English, French, German, Italian Subtitles: English, French, German, Italian, Dutch
Keywords: Tv Series -- Drama